Emergent - Cohn, Rachel (Cohn, Rachel. Beta novel., 2014)
Elysia has finally learned that she has a soul and although she knows it hurts Zhara, her First, that Alexander has chosen her as his life mate, Elysia cannot give him up and instead takes her place fighting by his side in the revolution of clones and humans against Denesme's twisted regime.